A day to bleed: exploring the effects of Zambia's Mother's Day policy on the representation of women in the financial sector - Chirwa, Memory Bwalya (Graduate School of Business (GSB), 2025)
This study examined how Zambia's menstruation leave policy, locally referred to as Mother's Day, influences the recruitment and retention of women in the financial and insurance sectors. As the only African nation to formalise menstruation leave, Zambia provided a distinctive context to explore the operation of gender-specific workplace policies within postcolonial African organisational settings. The research drew on qualitative data from 32 interviews with employees and managers across four organisations, revealing several key findings. Firstly, organisational size significantly shaped implementation approaches, with large organisations employing bureaucratic processes, medium organisations adopting hybrid practices, and small organisations favouring Ubuntu-inspired community-oriented methods. Secondly, a leadership policy paradox emerged, where senior women often avoided using menstruation leave to safeguard their professional credibility, thereby perpetuating stigma around its use. Thirdly, varying levels of cultural integration were observed, ranging from surface-level adoption to deeply embedded practices that reflected local values. Women adopted different strategies to navigate the policy, balancing health needs with career aspirations. These strategies highlighted the complicated interplay between professional identity, organisational context, and cultural dynamics. While the policy aimed to support women's workplace participation, its impact on recruitment and retention was nuanced, particularly when compounded by other types of leave such as maternity, sick, and study leave. Implementation challenges were shaped by implicit biases, practical difficulties, and societal stigma. This research contributes to the nascent discourse on menstruation leave policies in the Global South by extending Acker's (1990, 2006) theory of gendered organisations to postcolonial African contexts and applying the social ecological model to workplace policy implementation. It offers practical recommendations for organisations, including the development of size appropriate implementation guidelines. The findings underscore the need for gender-specific policies to move beyond symbolic compliance, fostering genuine workplace equity.